Insights of take-off of ground reactions force in high jump - Martins, S.; Carvalho, J.; Conceicao, F. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The take-off plays an important role on the high jump (HJ) performance, since it is there where the trajectory of the centre of mass is defined (Tellez, 1993) in order to achieve the maximum possible height and clear the bar (Dapena, 1988). The literature has presented several studies using kinematic parameters, however there are very few studies using dynamic parameters to evaluate the take-off (Coh & Supej, 2008). In contrast to other jumps, the HJ presents an increased complexity due to the curvilinear approach-run pathway, imposing a three-dimensional analysis of the movement. On the other hand, the point where the jumpers perform the take-off differs considerably for different subjects. For those reasons research presented in the literature is fundamentally based in the kinematics of the approach-run and take-off. Although great knowledge was achieved in the kinematic of HJ, very few studies can be found concerning the ground reaction forces (GRF). However the knowledge of the GRF pattern enables a more thorough evaluation of the jumper technique and efficiency. The purposes of this study were (i) to evaluate the HJ take-off technique using force plate data based on the characterization of the GRF pattern and (ii) definition of take-off GRF profiles as function of technical and conditional characteristics of different athletes.